PENGGUNAAN BIJI KELOR (Moringa oleifera L.) DAN BIJI ASAM JAWA (Tamarindus indica L.) PADA PENJERNIHAN AIR SUMUR BOR MELALUI PROSES KOAGULASI DAN FLOKULASI DENGAN METODE SENTRIFUGASI - Pratiwi, Annisa Aulia; Masthura, Masthura; Husnah, Miftahul (JOURNAL ONLINE OF PHYSICS, 2023)
Drilled well water at the Ar-Rahmat Mosque in Manunggal Village, Labuhan Deli District, Regency Deli Serdang, North Sumatra Province, has a color that tends to be yellow and cloudy. From the test results, it was found that the turbidity level in the drilled well water reached 35.3 NTU and the iron (Fe) content reached 1.679 mg/L. This shows that the borehole water does not meet clean water standards according to PERMENKES RI No.32 of 2017, namely with a maximum turbidity level of 25 NTU and a maximum iron (Fe) content of 1.0 mg/L. There is one way to purify borehole water by using moringa seeds and tamarind seeds in the coagulation and flocculation processes through the centrifugation method. This study aims to determine the most optimal seed composition in purifying well water. The mass variations used in this study were moringa seeds and tamarind seeds each with a mass of 0.08 grams and 0.09 grams. In this study, the results of the most optimal seed composition for purifying borehole water were tamarind seeds at a mass variation of 0.08 gram with a turbidity value of 0.53 NTU and a value of iron (Fe) content of 0.0087 mg/L. This shows that the drilled well water that has gone through the water purification process meets the PERMENKES RI standard No. 32 of 2017.